Interactive interface and lighting graphic sesign using Wavelet-based objective function. - Nam, Hà Hải (Journal of Computer Science and Cybernetics, 2012)
Lighting design in computer graphics is essentially not a random process but one driven by both a technical and aesthetic appreciation of lighting in computer graphics. In some applications, the result of the lighting design process is a 2D image derived by rendering a 3D scene. Users with limited understandings of manipulation of lighting parameters may have difficulties in properly modifying the lighting parameters in order to achive desired lighting effects. We present and demonstrate an approach to lighting design in applications where the expected result of the lighting design process is a 2D image. In this approach, the lighting-by-example method using wavelet-based objective function is used in combination with an interactive interface in order to optimize lighting parameters for an object or a group of objects individually, and the visual results of these separate processes are combined (utilizing 3D depth information) in the seamless generation of a final 2D image.